Significance of Conformation Changes During the Binding and Release of Chromium(III) from Human Serum Transferrin. (29th May 2020) - Edwards, Kyle; Vincent, John
Abstract: Objectives: Transferrin, Tf, the protein that transports iron from the blood to the tissues via endocytosis, is believed to also transport chromium(III), Cr(III). Recently, the presence of multiple conformations was suggested by spectroscopic studies. The objective of this work is confirm whether various conformers of Cr(III)2 -Tf exist and their potential significance for Cr(III) transport. Methods: Cr(III) was added to apoTf in a buffered solution at pH 7.4 containing 25 mM bicarbonate at 37 °C. After time intervals, ultraviolet spectra were collected, or aliquots were removed and frozen for analysis by electron paramagnetic resonance (EPR) spectroscopy, which can distinguish free Cr(III) and Cr(III) bound to the two metal binding sites of Tf. To model the acidification of the endosome that triggers release of metal ions from Tf, the Cr(III)2 -Tf conformer solutions were acidified by the addition of hydrochloric acid to pH 4.5 or 5.5. At time intervals after acidification, samples were again analyzed by ultraviolet and EPR spectroscopies. Results: A combination of electronic and EPR studies reveal that the addition of Cr(III) to apoTf at near neutral pH in the presence of 25 mM bicarbonate results in the rapid binding of two Cr(III) accompanied and then followed by a series of conformation changes in Cr(III)2 -Tf. These multiple conformations give rise to different spectroscopic properties and upon acidification different rates of Cr(III) release. Conclusions: The conformer of Cr(III)2 -Tf used in most previous studies and giving rise to EPR features at g ∼ 5.1, 5.4, and 5.6 forms too slowly to be physiologically relevant; however, two previously unknown conformers of Cr(III)2 -Tf, giving rise to an EPR feature at g ∼2 and at g ∼ 5.4, respectively, were identified. The latter of these conformers has a lifespan similar to the turnover time of transferrin and releases Cr(III) rapidly, suggesting it is probably the most physiologically significant conformer of Cr(III)2 -Tf. Funding Sources: The University of Alabama College of Arts and Sciences Research Award.